Industrial Development, Public Policy and Spatial Differentiation in Central Europe: Continuities and Change - Lux, Gábor (Discussion Papers, 2012)
In Central European states, the questions of industrialisation have been asked numerous times in relation to the European core. Before WW II, industrial underdevelopment could be linked to the peripheral situation of Central European economies, and meaningful parallels could be drawn with the states of Southern Europe, who had faced the same problems. With state socialism and its focus on catch-up through industrial development, the issue became muddled. To what extent was the path taken by Central European states to industrialise comparable to other economies on the European periphery, and to what extent was it a specific outcome of socialist ideology? Furthermore, is it possible to speak about national models, or are these variations less significant? The role of industry had to be re-evaluated during transformation. Decline in employment, economic share and exports was universal, but it is also visible that some industrial activities have been able to survive and become a new source of growth. In Central Europe’s integration into European and global networks, Foreign Direct Investment (FDI) has reshaped space; however, it is apparent that the dichotomy between old and new industries is a questionable one: even new greenfield investments are closely linked to previous production millieus, while old industries have often shown ability to be revitalised. Therefore, the spatial structure of industry of Central Europe today is a patchwork of continuity and change, where convergence towards the core is just as possible as the recreation of traditional peripheral relationships. This paper aim to trace the development of Central European industry from three aspects: public policy (what was the role of the state in influencing industrial growth?), economic development (what role did industry play in national economies, and how did national models compare to each other and western models?) and spatial development (how did industrialisation and de-industrialisation processes play out in heterogenous space?). Three major time periods are considered: the inter-war years, state socialism and the present; and the question examined whether they represent breaks in development or continuities and organic transitions.